2023
DOI: 10.5713/ab.23.0049
|View full text |Cite
|
Sign up to set email alerts
|

Characterization analysis of Rongchang pig population based on the Zhongxin-1 Porcine Breeding Array PLUS

Abstract: Objective: To carry out a comprehensive production planning of the existing Rongchang pig population from both environmental and genetic aspects, and to establish a closed population with stable genetic diversity and strict pathogen control, it is necessary to fully understand the genetic background of the population.Methods: We genotyped 54 specific pathogen free (SPF) Rongchang pigs using the Zhongxin-1 Porcine Breeding Array PLUS, calculated their genetic diversity parameters and constructed their families.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…First, we used chips for the SNP genotyping, which may have missed SNPs that were detected by whole-genome sequencing. Nevertheless, previous studies have shown that the Zhongxin-1 Porcine Breeding Array PLUS chip provided reliable estimates of genomic diversity and selection signatures in a comparative analysis between pig breeds [11]. Second, low-altitude Chinese indigenous pig breeds have considerable phenotype diversity due to the thousands of years of domestication and are therefore more genetically differentiated than the high-altitude Tibetan pigs.…”
Section: Detection Of Snps Between Highland and Lowland Tibetan Pigsmentioning
confidence: 99%
“…First, we used chips for the SNP genotyping, which may have missed SNPs that were detected by whole-genome sequencing. Nevertheless, previous studies have shown that the Zhongxin-1 Porcine Breeding Array PLUS chip provided reliable estimates of genomic diversity and selection signatures in a comparative analysis between pig breeds [11]. Second, low-altitude Chinese indigenous pig breeds have considerable phenotype diversity due to the thousands of years of domestication and are therefore more genetically differentiated than the high-altitude Tibetan pigs.…”
Section: Detection Of Snps Between Highland and Lowland Tibetan Pigsmentioning
confidence: 99%
“…However, this homogenized breeding strategy has overshadowed local pig breeds, such as the Rongchang pig (RC), Tibetan pig (T), and Wuzhishan pig (WZS). Despite slower growth and lower yields, these local breeds demonstrate unique advantages in disease resistance, reproductive efficiency, and adaptability to harsh environments, and their meat also boasts distinctive flavors [ 14 , 15 , 16 ]. Additionally, local pig breeds hold considerable advantages as experimental models due to their genetic diversity and adaptability, which are vital for researching disease models relevant to humans [ 17 ].…”
Section: Introductionmentioning
confidence: 99%